The impact of proper information management and data storage for long term decision-making business process and risk mitigation at MNCs – A perspective from Chevron Bangladesh - Sumaya (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.